Anti-Toxoplasma gondii effect of two spider venoms in vitro and in vivo. (August 2019) - Hou, Shengjie; Liu, Yuan; Tang, Yaqin; Wu, Mengqi; Guan, Jianwu; Li, Xianyao; Wang, Zheng; Jiang, Jinying; Deng, Meichun; Duan, Zhigui; Tang, Xing; Han, Xiaoqing; et al.
Abstract: Toxoplasma gondii ( T. gondii ) is an important pathogen that can cause serious public health problems. Currently, therapeutic drugs for toxoplasmosis present serious side effects, researches on more effective and novel substances with relatively low toxicity are urgently needed. Spider venoms comprise diverse novel pharmacological compounds. However, the anti- T. gondii activity of spider venoms remains largely unknown. This study was carried out to evaluate the anti-parasitic effect of spider venoms from Ornitoctonus huwena (HWVM) and Chilobrachys jingzhao (JZVM) against T. gondii tachyzoites in vitro and in vivo. Cytotoxic activity of HWVM and JZVM to HeLa cells was determined by MTT cell viability assays. Low doses (3.125, 6.25 and 12.5 μg/mL) of HWVM and JZVM displayed low toxicity to HeLa cells. Trypan blue exclusion assay indicated that either of HWVM and JZVM affected the viability of tachyzoites in a time-dependent manner. Both spider venoms inhibited the invasion and proliferation of tachyzoites in vitro ( p  < 0.05). Moreover, Mice treated with HWVM after infection with 2 × 10 3 T. gondii tachyzoites showed a better survival rate than mice treated with saline alone ( p  < 0.05), while mice treated with JZVM did not. Our findings indicate that HWVM is a promising agent for the treatment of toxoplasmosis. Highlights: In vitro, HWVM or JZVM can effectively inhibit the invasion and proliferation of T. gondii. In vivo, HWVM can significantly prolong the survival time of mice infected with T. gondii. HWVM is a promising agent for the treatment of toxoplasmosis.